Acceptability and feasibility of a virtual community of practice to primary care professionals regarding patient empowerment: a qualitative pilot study - Carlos Jesús Bermejo-Caja; Débora Koatz; Carola Orrego; Lilisbeth Perestelo-Pérez; Ana Isabel González-González; Marta Ballester; Valeria Pacheco-Huergo; Yolanda del Rey-Granado; Marcos Muñoz-Balsa; Ana Belén Ramírez-Puerta; Yolanda Canellas-Criado; Francisco Javier Pérez-Rivas; et al. (BMC, 2019)
Abstract Background Virtual communities of practice (vCoPs) facilitate online learning via the exchange of experiences and knowledge between interested participants. Compared to other communities, vCoPs need to overcome technological structures and specific barriers. Our objective was to pilot the acceptability and feasibility of a vCoP aimed at improving the attitudes of primary care professionals to the empowerment of patients with chronic conditions. Methods We used a qualitative approach based on 2 focus groups: one composed of 6 general practitioners and the other of 6 practice nurses. Discussion guidelines on the topics to be investigated were provided to the moderator. Sessions were audio-recorded and transcribed verbatim. Thematic analysis was performed using the ATLAS-ti software. Results The available operating systems and browsers and the lack of suitable spaces and time were reported as the main difficulties with the vCoP. The vCoP was perceived to be a flexible learning mode that provided up-to-date resources applicable to routine practice and offered a space for the exchange of experiences and approaches. Conclusions The results from this pilot study show that the vCoP was considered useful for learning how to empower patients. However, while vCoPs have the potential to facilitate learning and as shown create professional awareness regarding patient empowerment, attention needs to be paid to technological and access issues and the time demands on professionals. We collected relevant inputs to improve the features, content and educational methods to be included in further vCoP implementation. Trial registration ClinicalTrials.gov, NCT02757781. Registered on 25 April 2016.